A Study on Cryptocurrency Investors’ Purchase Intentions: Revisiting the Brand Personality Theory - Chittineni, Jyothi (International Journal of Economics and Financial Issues, 2022)
This paper aims to identify the factors affecting the investment decision of retail investors to add crypto assets to their portfolios. The personality theory and the innovation diffusion theory are used in this study to understand the characteristics that influence investors' buying intentions. The study results show that the retail investors' purchase intentions are influenced by familiarity with the asset, trust, risk and return profile of the asset class, and the perceived security of the investor. The study also examines the role of innovativeness as a moderating variable in the relationship between purchase intentions and the primary variables. The study confirms that innovativeness has a significant mediating role in the relationship between purchase intentions and trust and also in the relationship between purchase intentions and perceived security. The results indicate that innovativeness has no significant moderating impact on the relationship between purchase intentions and familiarity and also on the relationship between purchase intentions and risk and return consciousness.